2022
DOI: 10.1177/20552076221133699
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in lysine methyltransferase 2C and PEG3 are associated with tumor mutation burden, prognosis, and antitumor immunity in pancreatic adenocarcinoma patients

Abstract: Background As a common cancer-related death worldwide, pancreatic adenocarcinoma (PAAD) has significantly increased mortality in recent years. In recent years, tumor mutation burden (TMB) has been regarded as the most popular biomarker for PAAD immunotherapy. However, it remains unclear which gene mutations affect TMB and immune response in pancreatic adenocarcinoma. Methods The somatic mutation images of PAAD samples were downloaded from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…CDK6 mutation may serve as an independent biomarker of poor prognosis in GC. 20 KMT2C, a histone methyltransferase involved in transcriptional coactivation, is a commonly mutated gene in pancreatic cancer 21 and in resectable diffuse gastric adenocarcinoma. 22 In previous studies, ERBB2 has been identified as an important mutation target in GC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CDK6 mutation may serve as an independent biomarker of poor prognosis in GC. 20 KMT2C, a histone methyltransferase involved in transcriptional coactivation, is a commonly mutated gene in pancreatic cancer 21 and in resectable diffuse gastric adenocarcinoma. 22 In previous studies, ERBB2 has been identified as an important mutation target in GC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the predictive accuracy of the gene features, a risk factor correlation diagram was constructed, and subsequent analyses including Kaplan–Meier analysis and time receiver operating characteristic curve (ROC) analysis were performed. R, version 4.0.3 (R Foundation, Vienna, Austria) with the “survival”, “survminer”, and “glmnet” packages was utilized to conduct the aforementioned analyses 12 …”
Section: Methodsmentioning
confidence: 99%
“…R, version 4.0.3 (R Foundation, Vienna, Austria) with the "survival", "survminer", and "glmnet" packages was utilized to conduct the aforementioned analyses. 12…”
Section: Establishment Of a Prognostic Hub Gene Signaturementioning
confidence: 99%
“…Expanding on this, Huang et al explored the role of KMT2C mutations in PDAC [163]. Their research emphasized tumor mutation burden (TMB) as a predictive biomarker for immunotherapy response, particularly with ICBs targeting PD-L1 and CTLA-4 proteins [164,165].…”
Section: Immune Checkpoint Therapymentioning
confidence: 99%